PENGARUH EDUKASI MELALUI BUKU SAKU TERHADAP PENGETAHUAN IBU RUMAH TANGGA MENGENAI DBD (Politeknik Kesehatan Kemenkes Bandung, 2021)
Dengue fever is a health issue that requires more attention, because dengue fever caused a significant mortality rate and included as an outbreak. Up until 2019, dengue fever cases kept on increasing in Indonesia along with multiple regions inside it. One of the reasons on dengue fever’s morbidity rate in Indonesia is still surging because the common knowledge among the citizens about dengue fever are still considered insufficient. This research was conducted to study on the influence of education through booklet towards housewife’s knowledge about dengue fever. This study used quasi-experiment with one group pre-test post-test method. 33 housewives were selected as samples in the study. Univariate analysis conducted using mean formula and bivariate through Wilcoxon. The study showed that the average pre-test score was 62.70 and post-test score increased by 28,57 with a total average score of 91,27. The Wilcoxon also showed there was a significant impact caused by education through booklet towards housewife’s knowledge about dengue fever with p value = 0.000 < 0.05. Education through booklet towards housewife’s knowledge about dengue fever was proven impactful towards housewife’s knowledge about dengue fever in RT 03. Pocket book “Kantong Ajaib” can be used by people’s in RT 03 as learning media.